Problems of using artificial intelligence in writing scientific research among fourth year students of Garmian University from their perspective. - علی, د. هیوا غفار (Sulaimani Journal for Humanities, 2025)
This study aims to identify the problems of using artificial intelligence in scientific research writing and provide appropriate solutions to mitigate them. The emergence of artificial intelligence has revolutionized many areas of life, including scientific research. Artificial intelligence is characterized by its ability to process and analyze massive amounts of data and information efficiently and accurately, provide in-depth insights, and accelerate the process of writing scientific papers. The development of artificial intelligence is not just a technological journey; it is an expansion of scientific research itself in academic and scientific centers. Artificial intelligence can help researchers add more detail to their research plans and develop them with more attractive and effective designs. Of course, the scientific debate about the use of artificial intelligence in scientific research is of paramount importance. As we enter an era characterized by the convergence of technology and science, the integration of artificial intelligence into scientific research is inevitable and could represent a major transformation. The research sample included 45 students from the Department of Social Sciences at Garmian University. For example, 23 students were randomly selected. This study used a descriptive-analytical approach. Survey tools were used to collect data, and Pearson's correlation coefficient (t-test) was used to analyze the data to reach several scientific conclusions. Study results: 1. Most of the research samples showed that the use of artificial intelligence tools in the statistical analysis process resulted in scientific errors. 2. Most of the research samples reported that the information students obtained through artificial intelligence to write their research papers contained linguistic and spelling errors. 3. Most of the research samples confirmed that they did not receive training on scientific research methodology or software for using artificial intelligence in scientific research writing. 4. Most of the researchers in the study sample indicated that the use of artificial intelligence software helped reduce the time and effort required to complete scientific research.
Keywords: Problems; Artificial Intelligence; Scientific Research; Students; Social Sciences